LA-ICP-MS zircon geochronology of granulite xenoliths from the Geronimo Volcanic Field, SE Arizona: implications for crustal evolution since 2.4 Ga - Rader, Mikaela Alaine (Kansas State University, 2021)
Lower crustal granulite xenoliths entrained in alkaline basalts from the Geronimo Volcanic Field (GVF), SE Arizona, provide constraints on composition, structure, and age of the lower crust in the southern Basin and Range. The GVF is located in the Mazatzal Province, accreted to the southern margin of Laurentia at ~1.69-1.65 Ga. Previous work conducted in this area provided information on the petrology, geochemistry and geothermometry for the xenolith suite, but age constraints of the xenoliths were limited to Nd model ages, making it difficult to place the evolution of the lower crust in the broader context of the geologic history of the region. This project uses zircon U-Pb geochronology and Hf-isotope analysis to determine the age of formation of GVF lower crust, as well as provide evidence for subsequent tectonic events that impacted its composition. Samples for this suite range in composition from mafic meta-cumulates (plg + cpx ± opx ± ol ± sp) to metadiorites and quartzofeldspathic lithologies (plg + kspar + cpx + ox ± qtz ± opx). GVF xenoliths analyzed for U-Pb geochronology present three distinct zircon age populations at ~1.63-1.65 Ga, ~1.48-1.42 Ga, and ~76-2 Ma, with the majority of young ages concentrated between 35-25 Ma. Zircon U-Pb ages for quartzofeldspathic lithologies present evidence of an event at ~1.65 Ga, suggesting an age of formation consistent with the age of the Mazatzal terrane. However, one quartzofeldspathic zircon core was dated at 2.38 Ga, suggesting the presence of an older component during formation of the Mazatzal crust, possibly originating as cratonic Laurentian sediment. Two quartzofeldspathic xenoliths (MR-GN21-39 and MR-GN21-53) contain zircon cores with discordant U-Pb ages that trend toward ~1.48-1.42 Ga, suggesting modification of the Mazatzal terrane beginning at ~1.48 Ga, the onset of the Picuris Orogeny and widespread 1.48-1.35 Ga plutonism in the southwestern US. These same quartzofeldspathic samples present young ages ranging from ~50-15 Ma, suggesting later alteration of the Proterozoic terrane by Tertiary magmatism associated with Farallon slab subduction. Metadiorites, which were previously inferred to be ~ 1.4 Ga on the basis of whole rock Nd model ages, yielded zircon U-Pb ages ranging from ~76 to 2 Ma, suggesting an origin through thermal resetting of zircons in older Paleoproterozoic crust or addition of new juvenile melts that assimilated Paleoproterozoic crust during magmatic underplating in the Cenozoic. Zircon Hf isotope data from both quartzofeldspathic and metadiorite lithologies are consistent with mantle separation at 2.4 Ga, following an intermediate (¹⁷⁶Lu/¹⁷⁷Hf = 0.018) crustal isotope evolution path. The existence of positive εHf(t) values in Mesoproterozoic zircon cores of some quartzofeldspathic xenoliths suggest reworking of this older Paleoproterozoic crust sometime between the time of Mazatzal formation and the 1.4 Ga Picuris orogeny and/or the widespread A-type granite event that also occurred across Laurentia at about this time. Eocene to Oligocene age zircons have εHf(t) values that range from -17 to 0, suggesting significant lower crustal modification during Farallon slab subduction.
Keywords: Geochronology; Geochemistry; Granulite xenoliths; Mazatzal; Farallon